Increasing rates of Clostridium difficile infection in Mexican hospitals - Dávila, Laura Palau; Garza González, Elvira; Rodríguez Zulueta, Patricia; Morfín Otero, Rayo; Rodríguez Noriega, Eduardo; Vilar Compte, Diana; Rodriguez Aldama, Juan Carlos; Camacho Ortiz, Adrián (2017)
Introduction: The epidemiology of Clostridium difficile infection (CDI) has changed in the last two decades. There is a lack of information regarding incidence and severity of CDI, especially in the developing world. Methods: This was a retrospective and observational study from four hospitals of three Mexican cities. Patients were diagnosed with CDI when presented with loose stools and had at least one of the following tests positive: toxins assay, real-time PCR, or an endoscopic image compatible with pseudomembranous colitis. CDI was classified according to international guidelines. Demographic and clinical data as well as information regarding total hospital admissions, total length-of-hospital stay, and other variables related to hospitalization were gathered from the epidemiology and administration departments of each hospital. Results: A total of 2050 hospital beds were analyzed with 288,171 patients hospitalized accumulating 1,576,446 days of hospitalization during the study period. The average rate of CDI per 1000 hospital-days was lower than the rates reported in the US and Europe, although in 2015 CDI rates were almost persistently above the mean rate for the study period. More than half of PCR positive patients were ribotype 027. Conclusion: Hospital rates of CDI are increasing in Mexican hospitals with a predominance of infections caused by ribotype 027.